A Canonical Model for Interactive Unawareness - Aviad Heifetz; Martin Meier; Burkhard C. Schipper (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
Heifetz, Meier and Schipper (2005) introduced a generalized state-space model that allows for non-trivial unawareness among several individuals and strong properties of knowledge. We show that this generalized state-space model arises naturally if states consist of maximally consistent sets of formulas in an appropriate logical formulation.
Keywords: C72; C70; D82; D80; 330; unawareness; awareness; knowledge; interactive epistemology; modal logic; lack of conception; bounded perception